Lived Experiences on Varied Dimensions of Police Recruits’ Training and Practice Basis for Quality Police Performance - Julieta R. Magpantay; Alberto D. Yazon; Consorcia S. Tan; Lerma P. Buenvinida; Marcial M. Bandoy (Research Synergy Foundation, 2021)
Police malpractice, abuse of power, and police misfits are issues and problems associated with police recruits. There were reports about inappropriate acts committed by newly hired police officers during their actual field practice. This qualitative phenomenological studydetermined the dimensions of training that hamper the development of knowledge and skills of the police trainees and police officers.Seventeen (17) purposely selected participants comprised the sample for this study. They were chosen through the following inclusion criteria: police supervisors, trainers, police recruits, staff from the National Police Training Institute (NPTI) and have two or more years ofexperience. Thirteen recurring themes emerged from the verbatim interviews. The Philippine National Police (PNP), National Police Training Institute (NPTI), and the National Police Commission (NAPOLCOM) are the three public safety institutions in the Philippinesthat are expected to promote the quality performance of police recruits in both training and practice. On the whole, the results of this study can serve as the basis for creating innovative policies about police recruits’ selection, curriculum development, stress management,creation of core competency framework, performance evaluation system, and training and practice needs assessment.